2012
DOI: 10.3727/096368911x580572
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Promotes Dopaminergic Differentiation in Induced Pluripotent Stem Cells and Inhibits Teratoma Formation in Rats with Parkinson-Like Pathology

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the degeneration of dopaminergic (DA) neurons in the midbrain. Induced pluripotent stem (iPS) cells have shown potential for differentiation and may become a resource of functional neurons for the treatment of PD. However, teratoma formation is a major concern for transplantation-based therapies. This study examined whether functional neurons could be efficiently generated from iPS cells using a five-step induction procedure combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 57 publications
0
37
0
1
Order By: Relevance
“…Earlier studies have described the positive influence of DHA on BDNF expression in vitro in induced pluripotent stem cells [89], and in the CNS [90][91][92]. Similarly to IL-6, the lowest concentrations of EPA resulted in an increase in BDNF levels that disappeared at higher concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have described the positive influence of DHA on BDNF expression in vitro in induced pluripotent stem cells [89], and in the CNS [90][91][92]. Similarly to IL-6, the lowest concentrations of EPA resulted in an increase in BDNF levels that disappeared at higher concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, we propose that it may be an alternative way to facilitate Nurr1 functions through activating or increasing those modulators. Inspiringly, RXR ligands, such as docosahexaenoic acid, bexarotene, LG100268 and XCT0139508 have been demonstrated to protect DA neurons through interaction with Nurr1/RXR heterodimers [87, 90, 91]. Although the biological functions of bexarotene still remains to be defined, one recent study has revealed that bexarotene might have the capacity to rescue the disrupted GDNF signaling and regulate oxidative phosphorylation and Nurr1-related genes [92].…”
Section: Prospect Of Nurr1-based Therapy For Pdmentioning
confidence: 99%
“…40 Our previous study demonstrated that suppression of c-Myc expression effectively blocked teratoma formation in rats transplanted with docosahexaenoic-acid-treated iPSCs 4 months after transplantation. 41 Therefore, exclusion of c-Myc would be a feasible way to reduce the incidence of tumor formation. In the present study, no tumor formation was observed in the recipients of non-c-myc iPSCs over 6 months.…”
Section: Figmentioning
confidence: 99%